Enhanced Cardiomyocyte NLRP3 Inflammasome Signaling Promotes Atrial Fibrillation. Issue 20 (13th November 2018) - Yao, Chunxia; Veleva, Tina; Scott, Larry; Cao, Shuyi; Li, Luge; Chen, Gong; Jeyabal, Prince; Pan, Xiaolu; Alsina, Katherina M.; Abu-Taha, Issam; Ghezelbash, Shokoufeh; Reynolds, Corey L.; et al.
Abstract : Background: Atrial fibrillation (AF) is frequently associated with enhanced inflammatory response. The NLRP3 (NACHT, LRR, and PYD domain containing protein 3) inflammasome mediates caspase-1 activation and interleukin-1β release in immune cells but is not known to play a role in cardiomyocytes (CMs). Here, we assessed the role of CM NLRP3 inflammasome in AF. Methods: NLRP3 inflammasome activation was assessed by immunoblot in atrial whole-tissue lysates and CMs from patients with paroxysmal AF or long-standing persistent (chronic) AF. To determine whether CM-specific activation of NLPR3 is sufficient to promote AF, a CM-specific knockin mouse model expressing constitutively active NLRP3 (CM-KI) was established. In vivo electrophysiology was used to assess atrial arrhythmia vulnerability. To evaluate the mechanism of AF, electric activation pattern, Ca 2+ spark frequency, atrial effective refractory period, and morphology of atria were evaluated in CM-KI mice and wild-type littermates. Results: NLRP3 inflammasome activity was increased in the atrial CMs of patients with paroxysmal AF and chronic AF. CM-KI mice developed spontaneous premature atrial contractions and inducible AF, which was attenuated by a specific NLRP3 inflammasome inhibitor, MCC950. CM-KI mice exhibited ectopic activity, abnormal sarcoplasmic reticulum Ca 2+ release, atrial effective refractory period shortening, and atrial hypertrophy. Adeno-associated virus subtype-9–mediated CM-specific knockdown of Nlrp3 suppressed AF development in CM-KI mice. Finally, genetic inhibition of Nlrp3 prevented AF development in CREM transgenic mice, a well-characterized mouse model of spontaneous AF. Conclusions: Our study establishes a novel pathophysiological role for CM NLRP3 inflammasome signaling, with a mechanistic link to the pathogenesis of AF, and establishes the inhibition of NLRP3 as a potential novel AF therapy approach. Abstract : Supplemental Digital Content is available in the text.